Unresolved questions in selection of therapies for treatment-naïve chronic lymphocytic leukemia - Rory Bennett; Mary Ann Anderson; John F. Seymour (Journal of Hematology & Oncology, 2023)
Abstract Background The treatment landscape for chronic lymphocytic leukemia (CLL) continues to undergo considerable evolution. Optimal selection of initial therapy from multiple effective options provides a major challenge for clinicians, who need to consider both disease and patient factors in conjunction with a view to sequencing available therapies in event of disease relapse. Review We explore the most topical clinically relevant unresolved questions through discussion of important available pertinent literature and propose expert opinion based on these data. (1) Shrinking role of chemoimmunotherapy (CIT); while novel therapies are generally superior, we highlight the utility of FCR for IGHV-mutated CLL. (2) Choosing between inhibitors of Bruton’s tyrosine kinase (BTKi); while efficacy between agents is likely similar there are important differences in toxicity profiles, including the incidence of cardiac arrhythmia and hypertension. (3) BTKi with or without anti-CD20 monoclonal antibodies (mAb); while obinutuzumab-acalabrutinib (AO) may confer superior progression-free survival to acalabrutinib (Acala), this is not true of rituximab (Ritux) to ibrutinib (Ib)—we highlight that potential for increased side effects should be carefully considered. (4) Continuous BTKi versus time-limited venetoclax-obinutuzumab (VenO); we propose that venetoclax (Ven)-based therapy is generally preferable to BTKi with exception of TP53 aberrant disease. (5) BTKi-Ven versus VenO as preferred time-limited therapy; we discuss comparable efficacies and the concerns about simultaneous 1L exposure to both BTKi and Ven drug classes. (6) Utility of triplet therapy (BTKi-Ven-antiCD20 mAb) versus VenO; similar rates of complete response are observed yet with greater potential for adverse events. (7) Optimal therapy for TP53 aberrant CLL; while limited data are available, there are likely effective novel therapy combinations for TP53 aberrant disease including BTKi, BTKi-Ven ± antiCD20 mAb. Conclusion Frontline therapy for CLL should be selected based on efficacy considering the patient specific biologic profile of their disease and potential toxicities, considering patient comorbidities and preferences. With the present paradigm of sequencing effective agents, 1L combinations of novel therapies should be used with caution in view of potential adverse events and theoretical resistance mechanism concerns in the absence of compelling randomized data to support augmented efficacy.